2014
DOI: 10.5194/acp-14-427-2014
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface meteorology during the Arctic Summer Cloud Ocean Study (ASCOS): evaluation of reanalyses and global climate models

Abstract: Abstract. Atmospheric measurements from the Arctic Summer Cloud Ocean Study (ASCOS) are used to evaluate the performance of three atmospheric reanalyses (European Centre for Medium Range Weather Forecasting (ECMWF)-Interim reanalysis, National Center for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) reanalysis, and NCEP-DOE (Department of Energy) reanalysis) and two global climate models (CAM5 (Community Atmosphere Model 5) and NASA GISS (Goddard Institute for Space Studies) M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
5
36
0
Order By: Relevance
“…In addition, the complete SEB contains turbulent fluxes as well, which can play an important role in energy exchanges between surface and atmosphere (Curry et al, 2000;Van Den Broeke et al, 2006;de Boer et al, 2014) and in mass-related processes such as sublimation (Thiery et al, 2012), in addition to the radiative fluxes considered here. Since turbulent fluxes cannot be retrieved from CloudSat and CALIPSO observations, these are not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the complete SEB contains turbulent fluxes as well, which can play an important role in energy exchanges between surface and atmosphere (Curry et al, 2000;Van Den Broeke et al, 2006;de Boer et al, 2014) and in mass-related processes such as sublimation (Thiery et al, 2012), in addition to the radiative fluxes considered here. Since turbulent fluxes cannot be retrieved from CloudSat and CALIPSO observations, these are not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nearsurface temperatures are kept constant at 263.48 K until 5 h to allow adequate time for model spin-up, after which they are forced to warm linearly, in hourly increments, to 265.66 K at approximately 11 h 20 min. This warming profile was artificially constructed based on approximated ERA-Interim (ECMWF reanalysis; Dee et al, 2011) 2 m temperature variations over the ocean in the Svalbard archipelago, close to the sea ice, during a cold-air outbreak (23 March 2013; see Young et al, 2016, 2017, andFig. S1 in the Supplement for further details).…”
Section: Model Set-upmentioning
confidence: 99%
“…Heterogeneous primary ice formation is represented using the D10 parameterisation with aerosol number concentrations calculated during the study by Young et al (2017). Previous studies (Harrington et al, 1999;Harrington and Olsson, 2001;Prenni et al, 2007;Morrison et al, 2012;de Boer et al, 2011;Young et al, 2017) have shown that the lifetime of springtime single-layer mixed-phase clouds at high latitudes is strongly dependent on N ice . Here, a lower (N ice = D10 × 0.5) and higher (N ice = D10 × 2) threshold are implemented to change the number concentration of modelled ice, and snow, particles.…”
Section: Test 3: Ice Number Concentrationmentioning
confidence: 99%
“…A high temporal and spatial resolution and a detailed microphysics scheme appear to be essential for representing the boundary layer and the gradients of various parameters, such as liquid water content, properly (Wesslén et al, 2014;de Boer et al, 2014;Solomon et al, 2015;Sotiropoulou et al, 2016). Several studies have also found that Arctic mixed-phase clouds, and their surface radiative effects, are sensitive to changes in CCN concentrations.…”
Section: Introductionmentioning
confidence: 99%